Ammonium Adsorption from Water by Macadamia Husk-Derived Biochar Forms: Mechanism and Behavior Study - Nguyen, Phuong Van (Indonesian Journal of Chemistry, 2025)
Ammonium (NH4+) is a nutrient and a pollutant of the aquatic environment. This study aims to evaluate the ability to recover NH4+ in water through the adsorption studies of macadamia husk-derived biochar at different pyrolysis temperatures (300, 450, and 600 °C). An experimental design was used to investigate adsorption conditions, including pH, biochar dosage, and NH4+ concentration in water, by letting biochar contact with NH4+ solution for about 2 h. Kinetic studies were also considered at different times. The results showed that the optimal parameters included pH 4, biochar dosage of 10 g L−1, and initial NH4+ concentration for saturated adsorption of 166.7 mg L−1. The highest NH4+ adsorption capacity of the three biochar forms ranged from 16.4 to 18.2 mg g−1, and the equilibrium time was 15–30 min. The Freundlich model is suitable for explaining the process behavior. Meanwhile, the pseudo-second-order kinetic model describes the mechanism of NH4+ adsorption process. The study provided a solution to utilize agricultural waste as an NH4+ adsorbent, as this adsorbed material can be used as fertilizer.